A new strategy for browning regulation: Flos Sophorae Immaturus extract and thermal treatment modulates nitric oxide and reactive oxygen species network in fresh‐cut potatoes - Qiao, Liping; Liu, Yuhan; Deng, Xiuli; Yu, Weiyang; Wang, Yanyu; Li, Xiaokui; Lu, Laifeng; Liu, Xia (Journal of food science, 2023)
Browning discoloration is a critical issue that negatively affects the quality of fresh-cut products and their industrial growth. Although many individual anti-browning technologies have been adopted, very few reports on the combination use of natural product extracts and physical methods exist. This study investigated the use of Flos Sophorae Immaturus extract in conjunction with thermal treatment and discovered that the combination effectively retarded browning in fresh-cut potatoes. Accordingly, the activities of polyphenol oxidase, peroxidase, and phenylalanine ammonia-lyase, as well as phenol accumulation, were effectively regulated. Meanwhile, this combination treatment also allowed for the modulation of nitric oxide synthase, superoxide dismutase, and catalase activities, while also regulating the concentrations of nitric oxide, superoxide anion, and hydrogen peroxide. Furthermore, the duplex treatment also regulated the antioxidant capacity and malondialdehyde concentrations. In addition, 39 phytoactive compounds, including protocatechuic acid, quercetin, (-)-alpha-pinene, and matrine, were identified in the extract, which may function as the anti-browning composition. These findings suggest that the combination technology modulated the dynamic equilibrium of production and clearance of nitric oxide and reactive oxygen species, thereby reducing browning deterioration. This is, to our knowledge, the first report of the combined application of Flos Sophorae Immaturus and thermal treatment, which may offer a novel option for fresh-cut preservation. PRACTICAL APPLICATION: The feasibility of integrating a novel highly efficient, safe, environmentally friendly, and easy-to-operate anti-browning alternative, with the ability to integrate into the existing processing line was investigated. The color of sliced potato chips was significantly improved (73.4%) by dipping them in a 0.01% Flos Sophorae Immaturus solution for 5 min and then in 55°C water for 2 min. In this regard, superior browning alleviation may depend on the regulation of the browning reaction and the NO-ROS network. This method has a promising future for making fresh-cut products more appealing to consumers and may provide guidance for fresh-cut producers and related industries.